2011
DOI: 10.1089/end.2010.0488
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Research Office of the Endourological Society Percutaneous Nephrolithotomy Global Study: Tract Dilation Comparisons in 5537 Patients

Abstract: The Global PCNL Study has identified differences in the method of dilation used between centers in Asia, Europe, and the United States. In the balloon dilation group, a total longer operative time and higher bleeding and transfusion rates were observed. The differences in outcome may be influenced by patient heterogeneity, including previous anticoagulation therapy or surgical procedures, in addition to the number of stones treated and rate of staghorn calculi, which were all higher in the balloon group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 35 publications
1
19
1
2
Order By: Relevance
“…12,14 In addition, separate analyses of the CROES PCNL Global Study database reported elsewhere have shown that significant increases in bleeding and transfusion requirements in patients undergoing PCNL are associated with a larger sheath size and longer operating times 15 and are more likely with balloon dilation compared with telescopic/serial dilation. 16 Interestingly, there was no significant difference between the two groups in terms of mean change in hemoglobin in the present study. The fluoroscopy group had a higher multiple puncture rate compared to the ultrasound group.…”
Section: Discussioncontrasting
confidence: 60%
“…12,14 In addition, separate analyses of the CROES PCNL Global Study database reported elsewhere have shown that significant increases in bleeding and transfusion requirements in patients undergoing PCNL are associated with a larger sheath size and longer operating times 15 and are more likely with balloon dilation compared with telescopic/serial dilation. 16 Interestingly, there was no significant difference between the two groups in terms of mean change in hemoglobin in the present study. The fluoroscopy group had a higher multiple puncture rate compared to the ultrasound group.…”
Section: Discussioncontrasting
confidence: 60%
“…Procedural failure rate was higher in the balloon dilatation group. [7] However, very frequent use of balloon dilators in the management of larger staghorn stones, and operations performed in different medical centers with various indications were limitations of this study.…”
Section: Discussionmentioning
confidence: 92%
“…[17,18] The Clinical Research Office of the Endourological Society (CROES) has recently published the outcomes of a study related to PCNL performed in 5803 patients from 96 centers worldwide. [7] Observational analyses demonstrated that when compared with the patients who had undergone Amplatz dilatation, in patients who had experienced balloon dilatation lower bleeding (9.4 vs. 6.7%) and transfusion rates (7 vs. 4.9%) were detected. Procedural failure rate was higher in the balloon dilatation group.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations